As far as you are able, join faith to reason: medieval attempts at reconciling faith to reason in Islam and christianity - Pawan Ahmad, Isham (University Malaya, 2010)
The questions “what is revelation?”, what does revelation tell us and what are its implications on man ?” are important questions for which we are still seeking answers even today. Does revelation give us knowledge that we cannot obtain by ourselves but once we hear it we can understand why it is true because there is some reasoning behind it? Or, does revelation gives us knowledge that is beyond our understanding, thus, we accept base on blind faith as true? Does revelation give us knowledge that is true because whatever God’s says becomes the truth? The answers to these questions would ultimately shape our Weltanshauung.For the Muslim philosophers, its major proponent, al-Farabi, sees revelation as the ultimate culmination of the highest intellectual truths transformed and put into a symbolic language with power to motivate man to right action. Revelation is capable to be understood by all and more importantly to drive and commit them to action. Aquinas adds a Christian dimension to this debate on the relationship of revelation to reason through his arguments for natural law. The need to investigate the relationship of revelation and reason and from this its implications on natural law and the future of the development of ethics has now an added dimension and importance .